2015
DOI: 10.1063/1.4917242
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ligands on the electronic and magnetic properties of Fe porphyrin in gas phase and on Cu(001)

Abstract: External electric field effects on electronic and magnetic properties at molecule-metal interfaces: Cuphthalocyanine adsorbed on Fe(001) surface J. Appl. Phys. 114, 083702 (2013); 10.1063/1.4819085 Adsorption geometry, conformation, and electronic structure of 2H-octaethylporphyrin on Ag(111) and Fe metalation in ultra high vacuum Time dependent density functional theory study of the near-edge x-ray absorption fine structure of benzene in gas phase and on metal surfaces

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The Hubbard U term was used to describe the d-states in iron . We employed a U eff = U – J = 3.0 eV, as it has been shown to accurately reproduce the electronic and magnetic structure of FeP in the gas phase. , In addition, a U eff of 3.0 eV has been successfully employed to study the adsorption of Fe­(II) porphyrins to surfaces. ,, Benchmark calculations showed that a U eff = 3.0 eV yielded the correct S = 1 ground spin state for FeP for all of the functionals considered herein.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Hubbard U term was used to describe the d-states in iron . We employed a U eff = U – J = 3.0 eV, as it has been shown to accurately reproduce the electronic and magnetic structure of FeP in the gas phase. , In addition, a U eff of 3.0 eV has been successfully employed to study the adsorption of Fe­(II) porphyrins to surfaces. ,, Benchmark calculations showed that a U eff = 3.0 eV yielded the correct S = 1 ground spin state for FeP for all of the functionals considered herein.…”
Section: Methodsmentioning
confidence: 99%
“…Nearly all 3d metals can be incorporated into the macrocycles, and they easily form noncovalent 2D assemblies on flat, crystalline surfaces, as well as 3D metal–organic frameworks. They have thus become a prototypical system for the study of coordination effects and molecular spintronics, as is evident by the large number of studies of metalated porphyrins on surfaces alone. , The local conductivity of the molecules correlates with the spin state of the central metal atom, ,,, and local probes, specifically scanning tunneling microscopes (STM), can be used to detect and manipulate the local magnetic properties. , Other effects conveniently observable on 2D porphyrin layers are adsorbate and substrate effects, such as superexchange between the metal centers through the substrate …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a deformation or buckling of the substrate next to the molecule is observed which is particularly pronounced for Cl and O ligands, while with O 2 as a ligand, the surface is much less affected. Indicating that for the dimer the interaction with the substrate is weaker than in the case of atomic Cl or O even though the adsorption distance is very similar, 2.28 Å (2.23 Å) with O 2 (O) for Cl the average distance between substrate and Fe is even larger (2.50 Å) [14]. In conclusion, it has been shown that the spin moment of FeP or the iron center itself can be tackled by the choice of the ligand in gas phase as well as on nonmagnetic Cu(001), whereby the changes for deposited molecules are even more expressed.…”
Section: Phthalocyanines and Some Current Applicationsmentioning
confidence: 94%
“…Having seen that for a sub-monolayer coverage of Fe OEP on Cu(001) 50% of the Cl atoms which remain after deposition of the surface is sufficient to cause significant changes in the magnetic behavior, a detailed study of possible ligands and their influence on the magnetic properties has been performed for free and deposited FeP molecules [14]. In gas phase, the influence of various combinations of porphyrin or phthalocyanine and ligands (axial or peripheral) has been investigated.…”
Section: Influence Of Ligandsmentioning
confidence: 99%